Projecting a Nostalgic Future: Nostalgia as Time Machine - Laks, Zoë (Cinémas)

(untitled) (Cinémas, 2021)
Nostalgia conjures the past, but what does it mean to be nostalgic for a future time? This article develops a theoretical model for a critical nostalgia for the future, one that sets both past and future at a temporal remove from the present, exposing both the longing and the impossible distance—the pain (algia)—that lies at the heart of all nostalgias. Using a case study on The Time Machine (George Pal, 1960), this article examines how to address three temporal problems that arise from nostalgias for the future, which seemingly lead to a regressive and deterministic model of futurity. Through a present-bound perspective and anachronistic logic, this film demonstrates how nostalgia for the future can reflexively reveal nostalgia’s inbuilt sense of distance, in order to unsettle linear and teleological conceptions of time and to open the possibility of an unwritten future.